Instinct As A Quranic Concept & Its Role In Islamic Pedagogy: A General Overview - Abdul Rahman Hussein Obeid; Syed Ahmad Tarmizi Syed Omar; Adnan Mohamed Yusuff; Muhammad Widus Sempo (Global Academic Excellence (GAE), 2024)
Volume 3 Issue 9 (December 2021) PP. 01-06 DOI: 10.35631/IRJSMI.39001